Production of certified reference materials for the sports doping control of the REV‐ERB agonist SR9009. Issue 2 (11th September 2018) - Davies, Stephen R.; Chan, Benjamin K.H.; Moawad, Michael; Garrett, Taylor R.; Brooker, Lance; Chakrabarty, Rima
Abstract: Two human metabolites of the REV‐ERB agonist SR9009, identified by researchers with an interest in sports doping control, have been synthesized and assessed for purity. The synthesis employed was a modification of published procedures for the parent SR9009, careful attention to the purification of intermediates and the final product ensuring materials of the highest purity were available for certification. For each candidate material impurities of related structure were identified and quantified as a relative mass fraction using high performance liquid chromatography–ultraviolet (HPLC–UV) detection and proton nuclear magnetic resonance ( 1 H NMR) spectroscopy. The quantification of water, occluded solvent, and inorganic residue was assessed using Karl Fischer, 1 H NMR, and thermogravimetric analysis, thereby completing the assessment of all impurities typically characterized by the mass balance approach. Summation and subtraction from 1000 mg/g afforded the mass fraction of the main component, the associated uncertainty ensuring certified reference material status can be applied to the resulting pure substance calibration standards. The availability of these standards to the sports doping control community will facilitate delivery of metrological traceability to the SI unit for mass (kg) to routine testing results and aid method development for the detection and quantification of SR9009 abuse. Abstract : Two human metabolites of the REV‐ERB agonist SR9009 have been synthesized and certified for purity using the traditional mass balance approach. For each candidate material the mass fraction of the main component is determined with established metrological traceability to the SI unit for mass (kg) thereby conferring certified reference material (CRM) status to the resulting calibration standards. Provision to the sports doping control community will facilitate method development for the detection of SR9009 abuse.